Critical success factors for new dishes in gastronomic offer of Belgrade restaurants - Božić, Aleksandar; Milošević, Srđan (Hotel and Tourism Management, 2021)
The subject of the research of this paper is the success of new dishes in the gastronomic offer of Belgrade restaurants, presented through critical success factors (CSFs) that can influence it. The aim was to analyze CSFs of new dishes in mentioned restaurants. The initial assumption was that the success of new dishes depends on various factors, which resulted in developing a general research question: What factors are important for the success of new dishes in the gastronomic offer of a restaurant? To achieve a high level standards in the restaurant industry and boost competitiveness, businesses have to keep up with modern trends and introduce innovative business approaches. The questionnaire consisted of three sections: managers’ profile, the restaurant profile and CSFs. The managers of Belgrade restaurants (N=64) were asked to rank ten different CSFs using the Likert scale. According to their opinions, seven CSFs were found to be very important for the success of new dishes.